Personal Extreme Programming with MoSCoW Prioritization for Developing Library Information System - Gita Marthasari; Wildan Suharso; Frendy Ardiansyah Ardiansyah (IAES Indonesia Section, 2018)
Software development projects require experience and knowledge of the developer or clients related to the system which will be developed. Unclear clients' needs potentially emerge many changes of needs during the process of development which can not be resolved by using conventional software development methodology. The implementation on the less significant requirements either from the clients or the system cause the development of the project took a long time. In this paper, we combine personal extreme programming (PXP) methodology with Moscow technique to overcome those problems. PXP is suitable to use in small to medium-sized projects if the clients do not know in detail about the needs in the development of application, application needed in relatively quick time, and the development phase is adjusted to use by a single programmer. Moscow technique was used for prioritizing requirements elicited in PXP methodology. Moscow is a method to determine priority needs based on cost, risk, and business value. This technique was applied during the planning phase of PXP to develop library application, thereby it reduced the time of project completion. The result was a library application suited the needs of clients to support business processes at Batu State Attorney's library.